Phosphatidylglycerols are induced by gut dysbiosis and inflammation, and favorably modulate adipose tissue remodeling in obesity. Issue 4 (4th January 2019) - Kayser, Brandon D.; Lhomme, Marie; Prifti, Edi; Cunha, Carla Da; Marquet, Florian; Chain, Florian; Naas, Isabelle; Pelloux, Véronique; Dao, Maria‐Carlota; Kontush, Anatol; Rizkalla, Salwa W.; Aron‐Wisnewsky, Judith; et al.
ABSTRACT: Lipidomic techniques can improve our understanding of complex lipid interactions that regulate metabolic diseases. Here, a serum phospholipidomics analysis identified associations between phosphatidylglycerols (PGs) and gut microbiota dysbiosis. Compared with the other phospholipids, serum PGs were the most elevated in patients with low microbiota gene richness, which were normalized after a dietary intervention that restored gut microbial diversity. Serum PG levels were positively correlated with metagenomic functional capacities for bacterial LPS synthesis and host markers of low‐grade inflammation; transcriptome databases identified PG synthase, the first committed enzyme in PG synthesis, as a potential mediator. Experiments in mice and cultured human‐derived macrophages demonstrated that LPS induces PG release. Acute PG treatment in mice altered adipose tissue gene expression toward remodeling and inhibited ex vivo lipolysis in adipose tissue, suggesting that PGs favor lipid storage. Indeed, several PG species were associated with the severity of obesity in mice and humans. Finally, despite enrichment in PGs in bacterial membranes, experiments employing gnotobiotic mice colonized with recombinant PG overproducing Lactococcus lactis showed limited direct contribution of microbial PGs to the host. In summary, PGs are inflammation‐responsive lipids indirectly regulated by the gut microbiota via endotoxins and regulate adipose tissue homeostasis in obesity.—Kayser, B. D., Lhomme, M., Prifti, E., Da Cunha, C., Marquet, F., Chain, F., Naas, I., Pelloux, V., Dao, M.‐C., Kontush, A., Rizkalla, S. W., Aron‐Wisnewsky, J., Bermúdez‐Humarán, L. G., Oakley, F., Langella, P., Clément, K., Dugail, I. Phosphatidylglycerols are induced by gut dysbiosis and inflammation, and favorably modulate adipose tissue remodeling in obesity. FASEB J. 33, 4741–4754 (2019). www.fasebj.org